NURSING PROFESSION IN THE CONTEMPORARY HEALTHCARE SYSTEM AND PUBLIC HEALTH: NEW ROLES AND CHALLENGES - Zivanovic, Dejan; Javorac, Jovan; Dimoski, Zvonko; Šumonja, Sanja (HEALTH CARE, 2021)
Given the general importance of caring for the health of the population, it is understood that the healthcare system is organizationally one of the most complex systems in a country, with elements that should provide physically, geographically, and economically accessible, integrated and quality healthcare. Historically, nursing as a profession has gone through several developmental stages, always trying to respond to professional challenges and follow modern trends and needs of society. By defining nursing as an integral and independent profession within the healthcare system, the modern nurse is faced with a number of professional, educational, and social challenges, especially in those countries where the nursing profession still has an inadequate social image, both in public and professional environment. The change of nurses professional role in reformed European and North American healthcare systems ̓ is particularly visible in primary health care and public health, where nurses have taken on one of the leading roles in the organization of the work process. With a unique professional focus that can be directed on the individual and family, or system and community, modern nursing as a healthcare profession is extremely well-positioned to respond to the need of modern society for the integration of health services and to make an active contribution to positive changes in the modern healthcare system, at the same time.